MECHATRONIC SYSTEM OF GRAIN COMBINE ADAPTIVE DRIVING CONTROL - Dmitry Yakovlevich Parshin; Denis Gennadyevich Shevchuk (Advanced Engineering Research, 2012)
The basic external actions on the grain combine mechatronic control system, and their effect on the motion pattern and the production process are considered. The research objective is the problem solution on the adaptive control of the motion path and tool load ratio of the grain combine based on fuzzy logic inference. A method of the mechatronic system driving control, and the algorithm of its implementation is proposed. The structure and the interconnection of the mechatronic system elements of the grain combine driving control are observed. The simulation model of the mechatronic system implemented in MatLab Simulink with Fuzzy Logic Toolbox, and the simulation results are given. The regression analysis results, and the quality assessment according to SSE by R-square and RSME approximation adequacy criteria are presented. Confidence intervals for the obtained parameter values are also calculated. The implementation of the grain combine mechatronic system is considered.